1991
DOI: 10.1042/bj2740855
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from a mutant β-lactamase for the mechanism of β-lactamase-catalysed depsipeptide aminolysis

Abstract: The Ser-70----Gly mutant of the TEM-1 beta-lactamase, where the active-site serine hydroxy group has been lost, does not catalyse the hydrolysis of either benzylpenicillin or N-(phenylacetyl)glycyl depsipeptides. This is as would be expected for a double-displacement mechanism where the Ser-70 becomes acylated at an intermediate stage. Further, however, the mutant enzyme, unlike the wild-type, does not catalyse aminolysis of depsipeptides by D-phenylalanine. If the active site is not structurally disrupted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The activity of the S70G -lactamases is higher than expected, suggesting the possibility of wild-type contamination. It has been suggested that in the resulting S70G mutant with single nucleotide change from the original Ser codon (AGC) to the glycine codon (GGC) that mistranslation of the glycine codon back to AGC leads to wild-type contamination (Mazzella et al, 1991). The same study has shown that the Table 3 Selected active-site distances in the wild-type and the mutant S70G -lactamase (Å ).…”
Section: The Catalytic Activity Of the S70g Enzymementioning
confidence: 99%
See 3 more Smart Citations
“…The activity of the S70G -lactamases is higher than expected, suggesting the possibility of wild-type contamination. It has been suggested that in the resulting S70G mutant with single nucleotide change from the original Ser codon (AGC) to the glycine codon (GGC) that mistranslation of the glycine codon back to AGC leads to wild-type contamination (Mazzella et al, 1991). The same study has shown that the Table 3 Selected active-site distances in the wild-type and the mutant S70G -lactamase (Å ).…”
Section: The Catalytic Activity Of the S70g Enzymementioning
confidence: 99%
“…glycine codon GGG having a double-nucleotide mismatch prevents wild-type contamination and reduces the activity of the S70G mutant -lactamase 50-fold (Mazzella et al, 1991). For this study, a second construct of the S70G mutation was made using the preferred glycine codon for E. coli, GGG, having a double nucleotide change.…”
Section: The Catalytic Activity Of the S70g Enzymementioning
confidence: 99%
See 2 more Smart Citations
“…Jamin et al (1993) have concluded that depsipeptides may also bind to a second site on acyl enzymes formed on reaction between the same depsipeptide and the Streptomyces R6 1 DD-peptidase. This is likely true for the P99 P-lactamase also (Mazzella et al, 1991).…”
Section: Discussionmentioning
confidence: 93%